Implementasi Metode Pembelajaran Aktif Dalam Meningkatkan Pemahaman Siswa Kelas XII Pada Mata Pelajaran Akidah Akhlak Di Madrasah Aliyah Tahfizil Qur’an Medan - Khairani, Aulia; Ruslan, Muhammad (Journal of Sustainable Education, 2025)
This research aims to describe the implementation of active learning methods in improving students' understanding of Moral Aqeedah in class XII Madrasah Aliyah Tahfizil Qur'an Medan Yayasan Islamic Center. Based on research results, the application of active learning methods through the stages of material preparation, selection of methods, media, and strategies, implementation (teacher as facilitator, discussion activities, presentations, and case studies), as well as evaluation (tests, attitude observations, projects, and authentic assessments) can increase student engagement. Students become more active in asking, arguing, and working together, as well as having a deeper understanding of the concept of Aqidah Akhlak. They can also connect the material with everyday life, so that Islamic moral values ​​can be internalized more effectively. Factors supporting the application of this method include the support of the madrasah environment, the availability of infrastructure, and the readiness of teachers. Meanwhile, the obstacles faced are time constraints, variation in students' abilities, and the habit of lecture methods that are still attached. Overall, active learning proved to be effective not only in improving students' cognitive understanding, but also in strengthening their Islamic attitudes and behaviors in accordance with the educational goals of Aqidah Akhlak.